Techno-Magism Media, Mediation, and the Cut of Romanticism - Wang, Orrin N. C., 1957- (Book collections on Project MUSE., 2022)
"Techno-Magism explores how British Romantic literature abuts and is organized around both print and non-print media. The book explores not only the print, pictorial art, and theater of early nineteenth-century England and Europe but also communicative technologies invented after the British Romantic period, such as photography, film, video, and digital screens. This proleptic abutting points to one way we can understand the implicit exceptionality wagered by reading Romanticism through media studies and media theory. Techno-Magism argues that both media studies and the concept of mediation in general can benefit from a more robust confrontation with, or recovery of, the arguments of deconstruction, an unavoidable consequence of thinking about the relationship between Romanticism and media. The book thinks that relationship through the catachrestic practice of a techno-magism, a technics of inscription always outside the causalities of a dialectical economy. The book further pursues two interrelated ideas: the structural incommensurability of the cut and the unapologetic presentism of the constellation. Marked by its late capitalist moment of composition, the book explores the continuity between the social character of Romantic and post-Romantic media, in terms of commodity culture, revolution, and the ecological devastation of the anthropocene"--